Luci e ombre di un documento controverso: la Correctio Filialis de Haeresibus Propagatis. Alcuni profili di diritto pubblico della Chiesa (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Una premessa circa il contesto e le motivazioni della lettera al Pontefice - 2. La Correctio Filialis de Haeresibus Propagatis: punto di arrivo o di inizio di un dibattito? Antecedenti storici e parallelismi da precisare nelle argomentazioni degli estensori - 3. Un bersaglio polemico non sorprendente: l’Esortazione Amoris Laetitia. Questioni pastorali e contrapposizioni tra visioni diverse sul diritto della Chiesa - 4. Lo stylus del Pontificato. Temi giuridici e prospettive future per lo studio dell’ordo iuris ecclesiae: prime conclusioni.Lights and shadows of a controversial document: the "Correctio filialis de haeresibus propagatis". Some outlines in Public Canon Law. ABSTRACT: The aim of this essay is to study and to analyze the current debate about recent Pope Francis’s propositions and affirmations regarding the Roman catholic doctrine and the concrete development of religious marriages in secular societies. One of the most important documents disputing the latest reforms and measures could be considered the so called “Correctio Filialis de Haeresibus Propagatis” that is intended to be a sort of manifesto of dissatisfaction and disappointment against the renewal of a comprehensive and tolerant approach in Canon Law’s rules concerning the status of divorced people and the assumed “irregular” civil unions. In spite of underlining some important aspects, probably not completely deepened by the Pope, that document at the same time undervalues the conceptual efforts to make the doctrine adequate to answer to a typical sense of restlessness in our time, even from a legal point of view.
Keywords: Diritto canonico